Hubungan Antara Foot Index Postrue Dengan Osteoarthritis Lutut - Bauw, Marjan, Agus Widodo, S.Fis, M.Kes (2017)
Backround : osteoatrhritis is a damage disease in which in the jiont cartilage are found,and in the long term can change the structure anatomy for damage to cartilage damage. Foot posture index is used as a gauge to determine the normal anatomty of the foot and least in this case the ankle joint. The aim of research : to the terminate of the relationship ofthe valeu of the index foot posture white knee osteoarthritis. Methode of research : using the chi- square test whit bivariate analysis. Sample 30 responder patients whit ostoarthritis of the knee in the general hospital of the wst papua fakfak province. Do one measurement result obtained from the value of p = 0,05 Conculcion : the is effect between footposture index in patient whit osteoarthritis of the knee. Keyword : osteoarthritis , the influence of the valeu in foot posture indx.